Zein functionality in viscoelastic dough for baked food products. (July 2021) - Bean, S.R.; Akin, P.A.; Aramouni, F.M.
Abstract: Zein is the major prolamin storage protein of maize and isolated zein is one of only two prolamins available commercially. Zein has a long history of use in the production of a wide range of materials including films, coatings, and fibers. Zein also has the unique ability to form viscoelastic dough with wheat-like properties when mixed with water under appropriate conditions. The ability to form such dough provides zein with the potential to be used in the production of baked food products for the gluten-free industry, in portions of the world where producing wheat is difficult or importing wheat is expensive, and in novel applications for plant-based foods in general. This article discusses factors that impact zein viscoelastic dough formation including the role of protein secondary structure, methods for improving zein dough formation as well as the production of breads and noodles from zein viscoelastic dough. Graphical abstract: Image 1 Highlights: Isolated zein proteins can form viscoelastic wheat-like dough when mixed at temperatures above Tg. Changes to protein secondary structure and protein interactions are important in dough formation. Several additives improve properties of zein viscoelastic dough. Viscoelastic zein dough by itself does not retain gas well. Hydrocolloids improve zein dough and bread quality.